Answer:
Therefore the required Equations are
[tex]y =2(x+3)\ \textrm{is the required expression for First condition.}\\y = 3x-2\ \textrm{is the required expression for Second condition.}[/tex]
Step-by-step explanation:
Given:
'y' represents the larger number and
'x' represents the smaller number
Then, a larger number is double the sum of 3 and a smaller number will be
Larger no = double of ( 3 and smaller number)
∴ [tex]y=2(x+3)\ \textrm{is the required expression for First condition.}[/tex]
Now,
The larger number is 2 less than 3 times the smaller number.
Larger number = 3 times smaller number and 2 less
∴ [tex]y=3x-2\ \textrm{is the required expression for Second condition.}[/tex]
Therefore the required Equations are
[tex]y =2(x+3)\ \textrm{is the required expression for First condition.}\\y = 3x-2\ \textrm{is the required expression for Second condition.}[/tex]